(untitled) (Fiep Bulletin - online, 2011)
The following article is a product of theoretical reflection, which arises as a proposal for a model of teacher training. Within the Physical Education teacher is one of the most important and most can influence it develops properly. This should make us reflect deeply on the most appropriate training, the characteristics that educators should have them and the philosophy that should be of about the same. The need for physical education teachers, acting as holistic educators is already raised by some authors for quite some time (Lopez Cuadra, 1968). This implies that the teacher must know what he teaches, know teach and educate, all in an integrated manner. Authors such as Krause (1994) see the teacher with a figure that should help learners to improve their personal training and comprehensive. It stresses the importance of orienting the educational processes from a multimodal perspective that promotes the construction of different representations by the students and against which teachers act intentionally and consciously in their teaching. The design of educational environments (DAE), includes processes of metacognition, conceptual development, preliminary ideas, history and epistemology, conceptual development, relationships CTS, and emotion and affection, these classes allow the teacher to the acquisition, comprehension, retention and application of what is learned, and his influence is also on the effectiveness of learning, critical thinking and problem-solving.